Wykorzystanie foresight w przewidywaniu przyszłości organizacji - Skonieczny, Jan (Foresight application in the future foreseeing of organization, 2006)
The paper focuses on the description of the foresight process. The author presents national foresight, regional foresight and corporate foresight. The foresight is a useful tool for policymakers on both the national and regional level and also for managers in corporate organizations.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 150-156